Integrasi Pendekatan Student Centered Learning Aktif dengan Media Pembelajaran Digital dalam Pembelajaran Akuntansi untuk Meningkatkan Pemahaman Konsep Mahasiswa (Lembaga Pengembangan Kinerja Dosen, 2026)
The rapid development of digital technology has created a growing need for innovative learning approaches that can enhance student engagement and deepen conceptual understanding. This need is particularly evident in accounting courses, which are still frequently delivered through traditional lecture-based methods. Therefore, this study aimed to examine the effectiveness of implementing an active Student-Centered Learning (SCL) approach integrated with digital learning media in improving students’ conceptual understanding. The study employed a quasi-experimental method using a pretest–posttest control group design. The participants consisted of 108 second-semester students from the Accounting Education Study Program who were divided into an experimental group and a control group. The research instruments included a conceptual understanding test, an observation sheet to monitor learning activities, and a questionnaire to capture students’ responses. The findings revealed that the experimental group achieved a higher mean posttest score (82.7) compared to the control group (74.1), with the difference being statistically significant (p < 0.05). Furthermore, the N-Gain score for the experimental group was categorized as moderate (0.50), while the control group showed a low category (0.26), with a large effect size (d = 1.02). Observational data also indicated an increase in students’ participation during the learning process, and approximately 87% of students reported that the material was easier to understand through case-based discussions supported by digital media. In conclusion, the integration of an active SCL approach with digital learning media proved to be effective in enhancing students’ conceptual understanding in accounting learning.